VD_FINDINFO Jug / 2013 / 75 vom 5. Juli 2013 - VD Tribunal cantonal (2013)
VENTE D'IMMEUBLE, CONTRAT MIXTE, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE | 197 al. 1 CO, 197 al. 2 CO, 197 CO, 200 CO, 201 al. 1 CO, 201 al. 3 CO, 201 CO, 205 al. 1 CO, 205 CO